Investigation of Procedural Decisions at the Beginning of Pre-Trial Investigation - Yа. A. Burlaka (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article studies one of the most important current topics from the point of view of practice – the decision of investigators to initiate a pre-trial investigation in criminal proceedings. It is emphasized that all further movement of criminal proceedings depends on the timeliness of the investigator’s decision to conduct a pre-trial investigation. Moreover, it is of great importance for the effective achievement of such a task of criminal proceedings as the speed and completeness of the investigation. It is determined that the guarantee of non-entry of information about a criminal offense in the Unified Register of Pre-trial Investigations is the right of the applicant to appeal against decisions, actions or omission of the investigator, prosecutor. At the same time, the absence of a legal requirement to make a procedural decision to initiate or to refuse a pre-trial investigation, in particular in the form of a ruling, does not always contribute to the exercise of the applicant’s right to appeal. It is confirmed by the relevant court decisions, which, unfortunately, currently takes place in practice. Based on the results of the study, possible ways to improve the current criminal procedural legislation of Ukraine on this issue are proposed.